2014
DOI: 10.3341/kjo.2014.28.3.275
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Bacterial Endophthalmitis Following Sustained-release Dexamethasone Intravitreal Implant: A Case Report

Abstract: A 58-year-old man admitted to our opthalmology department with the complaint of branch retinal vein occlusion. He was treated with intravitreal Ozurdex in the right eye. Two days after the injection, the patient presented with ocular pain and the visual acuity was hand movement. A diagnosis of endophthalmitis was made. We performed emergent pars plana vitrectomy (PPV) and the implant was removed from the vitreous cavity using a retinal forceps. A combination of vancomycin 1.0 mg and amikacin 0.4 mg was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…The other strategy would be, to remove the Ozurdex implant by pars plana vitrectomy. This has been described in a case of endophthalmitis following Ozurdex implant 4…”
Section: Discussionmentioning
confidence: 92%
“…The other strategy would be, to remove the Ozurdex implant by pars plana vitrectomy. This has been described in a case of endophthalmitis following Ozurdex implant 4…”
Section: Discussionmentioning
confidence: 92%
“…Anti-VEGF becomes the main treatment in the short term. However, it has some limitations: monthly injections are required, causing inconvenience; repeated injections lead to some difficulties, for example, wastage of time in treatment, increased risk of infection, intraocular inflammation, and so on [13]; and the treatment is also expensive for most patients. Therefore, another study found that RVO was also related to inflammatory cytokines causing inflammatory diseases, including chemokines, prostaglandins, matrix metalloproteinase, interleukins, selectins, vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), angiotensin II, and inflammatory cells (macrophages and neutrophils) [14].…”
Section: Discussionmentioning
confidence: 99%
“…We have not removed the implant initially, though many case reports highlighted the importance of Ozurdex ® removal. [789] We based our decision of not removing the implant on Stem et al . study which showed that is not necessary in all cases to perform vitrectomy or to remove the dexamethasone implant.…”
Section: Discussionmentioning
confidence: 99%